Effects of the Religious Factor on Socio-Political and Economic Processes in Egypt - Muhammadolim Muhammadsidiqov (Zien Journals, 2022)
This article analyzes influence of the religious factor in the political processes in Egypt, new approaches in Egypt’s policy on religion, social and economic factors that caused revolutions and outcomes of the “Arab Spring”.
Keywords: religious factor; political factor; revolution; Muslim Brotherhood